علاقة نظام الرقابة الداخلية بالقوائم المالية في البنوك التجارية (المجلة العراقية للعلوم الاقتصادية, 2018)
The reasearch aims to study and analyse the internal control system in the banks, through impose administrative and accounting and operational supervisory procedures on the internal environment of the bank, and clarifying how far the financial statements indicators used as a tool for publishing the necessary information for the users of the financial statements of the banks, and to contribute to know the ways of how to improve the financial statements to reach the required level of publishing information that should be published in the financial statements of the banks, according to international standards, and according to the international accounting standard No 30.